PENGATURAN DAN MENATA POLA RUANG DESA ULANTA KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - irwan wunarlan; Berni Idji; M. Faisal Dunggio; Satar Saman (Jurnal Pengabdian Teknik Industri, 2022)
Ulanta Village is an area in the middle of the city and most (81.84%) of the village area has been designated as a provincial strategic area in the 2014-2034 Bone Bolango Regency Regional Spatial Plan, namely Agropolitan Areas and Integrated Industrial Areas as a form of support for life community economy in Bone Bolango Regency. As for the Identification and Formulation of the Problem (1) Analyze community perceptions regarding the spatial pattern of the area in Ulanta Village, Suwawa District, Bone Bolango Regency, (2) Evaluate the suitability of the implementation of the spatial pattern for the Ulanta Village area with the RTRW of Bone Bolango Regency. (3) Making recommendations based on the results of an evaluation of spatial planning patterns in the Suwawa sub-district in Bone Bolango Regency. The target group in this science and technology implementation activity is the community, especially village government apparatus and youth youth organizations in Ulanta Village, Suwawa District, totaling 20 people. This activity takes the form of village spatial planning training by using village government officials and youth youth organizations in Ulanta Village, Suwawa District, which are very vulnerable to various land conversion problems.This training is an alternative solution to tackling environmental degradation and provides added value in increasing skills, insight and knowledge about the use of the environment to make it a comfortable and beautiful environment for the community. Keywords: Arrangement, spatial pattern, village, environment